1990
DOI: 10.1172/jci114443
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular cystine loading inhibits transport in the rabbit proximal convoluted tubule.

Abstract: Cystinosis is an autosomal recessive disorder characterized by a high intracellular cystine concentration. To establish an in vitro model of this disorder and examine the mechanism of the proximal tubule transport defect seen with elevated intracellular cystine concentrations, rabbit proximal convoluted tubules (PCT) were perfused in vitro. PCTs were loaded with cystine using cystine dimethyl ester, a permeative methyl ester derivative. Bath cystine dimethyl ester (0.5 mM) reduced volume absorption (JV) (0.67±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 17 publications
3
39
2
Order By: Relevance
“…So far with this model uptake measurements with radiolabeled solutes were performed in rat (10,18,31,34) and rabbit (11,13,14,32,33) proximal tubules and with cultured porcine LLC-PK 1 cells (15,19,30). These studies showed an inhibition of volume absorption (13,14), reduction of the transepithelial potential difference (13), and inhibition of transport of different solutes (7,10,(13)(14)(15). Most of proximal tubular transport is Na ϩ -coupled; depending therefore on the Na ϩ -gradient from the extrato the intracellular space, the role of energy metabolism, Na ϩ / K ϩ -ATPase activity, intracellular phosphate, and ATP levels in this experimental model have been investigated (14,18,31,33,34).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…So far with this model uptake measurements with radiolabeled solutes were performed in rat (10,18,31,34) and rabbit (11,13,14,32,33) proximal tubules and with cultured porcine LLC-PK 1 cells (15,19,30). These studies showed an inhibition of volume absorption (13,14), reduction of the transepithelial potential difference (13), and inhibition of transport of different solutes (7,10,(13)(14)(15). Most of proximal tubular transport is Na ϩ -coupled; depending therefore on the Na ϩ -gradient from the extrato the intracellular space, the role of energy metabolism, Na ϩ / K ϩ -ATPase activity, intracellular phosphate, and ATP levels in this experimental model have been investigated (14,18,31,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of volume reabsorption and a decrease in the lumen-negative transepithelial potential difference were shown under these conditions (13,14). Furthermore, inhibition of glucose, different amino acids, bicarbonate, and phosphate reabsorption in cystine-loaded proximal tubules was demonstrated (7,13). Inhibition of glucose transport was also shown in LLC-PK 1 cells (15).…”
mentioning
confidence: 87%
See 3 more Smart Citations